Inheritance Rights of Nasabiyyah Children Born Out of Wedlock According to Islamic Family Law - Maulana, Anas; Akbar, Zainuri; Habibie, Ramadhani Alfin; Norhadi, Muhammad; Hasuna, Kamal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The inheritance rights of nasabiyyah children outside of marriage, religion or the state will not get inheritance because the status of the child follows his mother, not his father. The serious problem is how to maintain the rights that should be obtained by children born out of wedlock, and whether the development of science and technology is ignored, even though in the rules of a change in a law is dependent on the time, place, and context of the problem. This study uses a comprehensive juridical law method that is comparatively analyzed to present data and facts from the perspective of positive law and Islamic law as well as the role of technology and science. The data is sourced from articles, books, legal rules and other juridical sources. This study concludes that in positive law, especially civil law of inheritance, the status of the child's inheritance rights outside of marriage can be recognized as long as the biological father recognizes the child's destiny as his destiny. As for Islamic civil law, there is no legal leniency for children outside of marriage, if the child is born without a clear status from both parents, then the child follows his mother and not his father. Islam has flexible laws that can adapt to the existing context. From the point of view of Islamic law, there are several ways to determine nasab, one of which is the qiyafah technique. The technique can be qiyas-kan with the reading of the nasab through a DNA test because it has almost the same legal 'illat. With the advancement of technology and the development of science, the method of determining the nasab can also be developed.